2024
DOI: 10.1021/jacs.4c01284
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Fungal P450 with an Unusual Two-Step Mechanism for Constructing a Bicyclo[3.2.2]nonane Skeleton

Huibin Xu,
Zhenbo Yuan,
Sai Yang
et al.

Abstract: The successful biomimetic or chemoenzymatic synthesis of target natural products (NPs) and their derivatives relies on enzyme discovery. Herein, we discover a fungal P450 BTG5 that can catalyze the formation of a bicyclo[3.2.2]nonane structure through an unusual twostep mechanism of dimerization and cyclization in the biosynthesis of beticolin 1, whose bicyclo[3.2.2]nonane skeleton connects an anthraquinone moiety and a xanthone moiety. Further investigation reveals that BTG5-T318 not only determines the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
0
0
Order By: Relevance
“…Biosynthetic studies have identified the fungal cytochrome P450 enzyme, BTG5, responsible for bicyclo[3.2.2]nonane skeleton formation during the biosynthesis of beticolin 1 21 from Cercospora species JNU001. 21 Mechanistic studies revealed a two-step process involving a common P450-catalysed heterodimerisation, followed by an uncommon redox-neutral cyclisation step. The total synthesis of ambruticins, polyketide-derived natural products from the myxobacterium Sorangium cellulosum , has provided standards for investigation of dihydropyran formation during their biosynthesis.…”
mentioning
confidence: 99%
“…Biosynthetic studies have identified the fungal cytochrome P450 enzyme, BTG5, responsible for bicyclo[3.2.2]nonane skeleton formation during the biosynthesis of beticolin 1 21 from Cercospora species JNU001. 21 Mechanistic studies revealed a two-step process involving a common P450-catalysed heterodimerisation, followed by an uncommon redox-neutral cyclisation step. The total synthesis of ambruticins, polyketide-derived natural products from the myxobacterium Sorangium cellulosum , has provided standards for investigation of dihydropyran formation during their biosynthesis.…”
mentioning
confidence: 99%